Phase change materials in building systems: an integrative literature review - Menezes Oliveira, Matheus (2022)
Phase Change Materials (PCMs) have a high latent heat storage capacity and the potential to provide thermal comfort to users and energy savings in buildings. However, many parameters must be analysed for the adequate selection and application of these materials. This article discusses the potential of applying PCMs in construction systems based on an Integrative Literature Review of national and international publications, identifying the classification, selection, incorporation and application criteria, trends, and research gaps. The review covers 134 articles, 103 of which are state-of-the-art from the past five years. Most of the research studies examined demonstrate that using PCMs in constructive systems leads to increased comfort hours and lower energy consumption. Climate conditions proved to be the most crucial parameter for an adequate choice of PCMs, highlighting a gap in the research on tropical regions with hot and humid climates and low latitudes, such as a large portion of Brazil. This study also detected a significant growth in research using multi-objective simulations and optimisation to simultaneously evaluate the parameters involved in the association of PCMs and building systems.